THE EFFECT OF DICE GAME IN TEACHING ENGLISH GRAMMAR AT MADRASAH TSANAWIYAH NEGERI 2 LABUHANBATU SELATAN - Hutauruk, Arferni Widya (BRIGHT VISION Journal of Language and Education, 2021)
This research was aimed to find out whether the students’ ability in English grammar taught by dice game is better than without dice game. The method of this research was quantitative method with the experimental research. The population of this research was the eight grade student which is distributed into two classes totally 60 students. There were 30 students in experimental class and there were 30 students in the control class. The finding of this research shows that teaching English Grammar by using dice game is effective. The mean of experimental class from pre-test was 50.33 and post-test was 67.17. It was also proved by tobserved (9.431) which is higher than ttable (1.671) in degree significance 5%. Furthermore, the hypothesis test that sign 2-tailed (p) was 0.00 while alpha (α) was 0.05 (0.00 < 0.005. It means that Ho was rejected and Ha was accepted. So, the students’ English grammar taught by dice game is better than without taught by dice game.